Communication optimization techniques for distributed virtual simulation - Koh, Alex Jit Beng. (2008)
This thesis addresses the problem of scalability in a Distributed Virtual Simulation (DVS) environment. DVS represents a class of simulations that is distributed over a network, operating with human participants who experience virtual representations of a realistic and complex "virtual world" in real time. Tremendous amount of bandwidth is required in attaining these large scale, realistic and complex simulations. Network communication latencies is identified as a major hindrance in overcoming the scalability hurdle. Recent developments in data communications drive two explorations presented in this thesis: 1) network-level multicasting, and 2) native ATM communications over high-speed ATM networks.